INSTITUTIONAL ENVIRONMENT OF THE NATIONAL QUALIFICATIONS SYSTEM IN THE RUSSIAN FEDERATION - Poryadina, Olga V.; Chernyakevich , Lidia M.; Andrianov, Yurii (Journal of Applied Engineering Science, 2020)
Methodological approaches to the organization of social and labour relations are systematized. The dynamics of the institutional environment of the labour market and vocational training system interaction in Russia is revealed. The peculiarities of the Russian experience of institutionalization of labour relations in the field of qualifications are shown. Post-industrial development of socio-economic systems, the processes of globalization, the transition of the Russian economy to an innovative model of development, the knowledge economy, the acceleration of scientific and technological progress and other objective challenges have necessitated the development of new human resource management mechanisms. In modern conditions the staff of an organization is considered to be the human capital, i.e. the field for strategic investments, a key factor in ensuring the competitiveness and sustainable development of the country, the region, the sector, the company rather than the costly part of the economy. Currently, one of the main problems of human resourcing for economic growth in the European Union and the Russian Federation is professional and qualification imbalance of supply and demand on the labour market. The National Qualifications System is aimed at solving the problems of linking the labour market with vocational training. Problematic aspects of development of the Russian National Qualifications System are marked.
Keywords: National Qualifications System; National Qualifications Framework; occupational standards; vocational training system; employment